Profiling the package traveler: An expenditure-based segmentation endeavor. (September 2021) - Zopiatis, Anastasios; Pericleous, Katerina
Abstract: An alternative to the specificities of geographic, socio-economic/demographic, and psychographic modes, expenditure-based segmentation, a behavioral approach, provides the ideal avenue for exploring tourist spending patterns and behavior. Reflecting the idiosyncrasies of a small island destination, this study explores tourists' actual spending in the course of their vacations in Cyprus. A two-step cluster analysis is utilized to develop an expenditure-based segmentation profile with the aim of exploring the spending behavior of tourists. Furthermore, econometric modeling reveals each cluster's effect on the relevant expenditure categories, and the net impact of the cost of package on spending at the destination. Noteworthy, expenditure at the destination is dissected into seven categories, thus providing a more thorough overview of tourist behavior. Findings reveal a five-cluster solution that profiles the spending behavior of package travelers, whereas segment comparisons highlight significant implications for local tourism stakeholders, on both the operational and strategic levels. Highlights: An expenditure-based segmentation profile of international package travelers is developed. Tourist expenditure is dissected into specific categories that fall outside the cost of the travel package. The similarities and differences of the expenditure behavior between the clusters are highlighted. The net impact of the cost of package on spending at the destination is investigated. Implications for industry stakeholders are discussed.